Victory Has a Thousand Fathers Sources of Success in Counterinsurgency - Paul, Christopher (RAND Corporation, 2010)
Insurgency is the most prevalent form of armed conflict and the subject of countless studies, yet the U.S. military has only recently begun to review doctrine and training in this area. An examination of approaches to counterinsurgency from 30 recent resolved campaigns reveals, for example, that good COIN practices tend to "run in packs" and that the balance of selected good and bad practices perfectly predicts the outcome of a conflict.